An Assessment on the Works of Charles Ambroisse Bernard the Founder of Mekteb-i Tıbbiye-i Adliye-i Şahane Imperial School of Medicine and His Effects on Ottoman - Öztürk, Hülya; Karasu, Cezmi (The Bulletin of Legal Medicine, 2014)
In the Ottoman State, modem medical education started in the early 19th century. The modem medical education first began in the Tersane Tibbiyesi (Shipyard Medical School), then continued in Tiphane (Medical School) and Cerrahhane-i Amire (Imperial Surgery School), and was then moved to a new building in Galatasaray and named as Mekteb-i Tibbiye-i Adliye-i Şahane (Imperial School of Medicine) in 1839. Dr. Charles Ambroisse Bernard, invited to the Ottoman State to ensure modernity in medicine, served as the director of Mekteb-i Tıbbiye-i Adliye-i Şahane and worked in Istanbul for the school until the end of his life. Dr. C. A. Bernard redesigned the school based on the example of Josephinum Military Academy of Medicine in Wien and strived to enable that Mekteb-i Tıbbiye-i Adliye- i Şahane offers medical education in the western style. The institution became a modem school with its library, botanical garden, pharmacy and midwifing classes. The first dissections and autopsies were performed in this school thanks to vigorous endeavors of Dr. C. A. Bernard, after special permission was received from the sultan of that age. During his life in Istanbul, Dr. C. A. Bernard produced many works. He lost his life due to inflammation in his neck in the last months of 1844. This study first emphasizes the importance of Dr. C. A. Bernard for medical practices in the Ottoman State and then provides information on four significant works he produced while working for development ofthe school. These works of Dr. C. A. Bernard, published in Turkey, are of particular importance since they serve to close a large gap in the field they deal with. Key words: Charles Ambroisse Bernard, Mekteb-i Tıbbıye-i Adliye-i Şahane, Composition.